Relative-clause increments and the management of reference: A multimodal analysis of French talk-in-interaction - Stoenica, Ioana-Maria; Pekarek Doehler, Simona (Amsterdam: John Benjamins, 2020)
In this paper we propose a reanalysis of relative clauses in French talk-in-interaction as part of “grammar for talk implementing action” (Schegloff, 1996:p.113). Our analytic focus is on relative clauses produced as increments, i.e., cases where the [main clause+relative clause] pattern emerges gradually, in response to interactional contingencies such as co-participants’ verbal and embodied conduct. We identify two recurrent interactional purposes that speakers accomplish by means of such self-incremented relative clauses: referential repair, ensuing from a recipient’s verbal and/or embodied display of trouble; referential elaboration, ensuing from a recipient’s verbal and/or embodied display of referent recognition. The findings challenge the notion of relative clauses as subordinate clauses, and extend our understanding of the emergent nature of grammar to the field of complex syntax.
Keywords: Relative clauses; Grammar-in-interaction; Increments; Repair; Embodied conduct